(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Currently, effective use of innovative technologies, advanced methods of world pedagogy in the educational process are urgent issues, and the project method incorporates advanced methods of education. The project method has the important task of mastering the existing experience and applying it at all stages of education during the training of a biology teacher. This article is devoted to the issues of development of research competence in students using the project method in the educational process.